RELATIONSHIP BETWEEN KNOWLEDGE LEVEL AND ATTITUDES OF DENTAL PROFESSION STUDENTS IN INFECTION CONTROL PROCEDURES AT THE RSIGM SULTAN AGUNG RADIOLOGY INSTALLATION DURING THE COVID-19 PANDEMIC - Pratama, Rahardian Aulia; Woroprobosari, Niluh Ringga; Sugiarto, Febia Astiawati (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Transmission in radiology facilities must be prevented by taking additional infection control precautions during the COVID-19 pandemic. A number of variables, including knowledge and attitudes, affect how an action is applied. The association between dentistry professional students’ knowledge and attitudes about the COVID-19 pandemic infection control protocol at the RSIGM Sultan Agung radiology installation is to be evaluated. Method: Analytic-observational research was used in this case, with a cross-sectional analysis of 139 samples. Validity and reliability tests have been done on the questionnaire. This study was conducted online using Google Forms for data collection, and SPSS 25 was used for the correlation test. Result: The results of the analysis show a significant correlation with a positive direction. Correlation strength (r) 0.263 indicates a weak correlation strength between the two variables. Conclusion: The conclusion of this study is that there is a relationship between these two variables. The implementation of infection control procedures at the Sultan Agung RSIGM radiology installation during pandemic COVID-19 from a knowledge and attitude perspective was still imperfect.